ANXIOGENIC EFFECT OF AN ATYPICAL ANTIPSYCHOTIC, OLANZAPINE IN PRE-CLINICAL MODELS - M, JAYARAJ; VERNON D’SOUZA, FLOYD (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Introduction: Atypical antipsychotics, such as olanzapine, act on multiple neurotransmitter pathways and produce complex central nervous system effects. Pre-clinical and clinical studies conducted in the past, to study their effects on anxiety, have come up with confusing and contradictory observations. Some studies have even indicated anxiogenic effect of these novel drugs. These observations are significant, because anxiety symptoms are known to be present in about 65% of schizophrenia patients. Any possible anxiogenic effect by one of the extensively used antipsychotic can have adverse impact on these patients. Hence, this study was undertaken with the aim of evaluating olanzapine for its effects on anxiety, in preclinical models. Methods: Rats of either sex weighing between 150 and 300 g were placed into three groups of six each. For 10 days, oral doses of the test drug (olanzapine 2 mg/kg), the control drug (distilled water), and the standard drug (diazepam 1 mg/kg) were given. The animals were taken for the elevated plus maze (EPM) and light dark arena (LDA) screening tests on the 10th day, 1 h after the compounds were administered. Results: Olanzapine treatment significantly reduced the amount of time that animals spent in open arms (p<0.05) of the EPM, and highly lighted compartments (p<0.05) of LDA, as compared to animals receiving control treatment, showing a significant anxiogenic impact. Conclusions: Olanzapine has exhibited potential to produce anxiogenic effect in preclinical models. Hence, it is suggested to use olanzapine with caution in patients of schizophrenia with anxiety symptoms.